Unveiling the Impact of Urban Green Landscape on Quality of Life in Kaduna, Nigeria: Residents' Perceptions and Sustainable Strategies - Ojobo, Henry; Oluwagbemiga , Paul Agboola; Shamang, Kasham Jummai (Alanya Üniversitesi, 2024)
This study investigates the influence of urban green landscapes on the Quality of Life (QoL) in Kaduna Metropolis, Nigeria, focusing on residents' perceptions and sustainable urban development strategies. Conducted from May to July 2023, the quantitative research surveyed 377 residents using a questionnaire. Statistical analysis, including correlation and t-tests, was performed using SPSS version 23. Findings reveal a positive perception of urban green spaces, significantly contributing to residents' QoL. Key results include high satisfaction with green areas enhancing environmental beauty (Mean=4.88, SD=0.90) and providing recreational appeal (Mean=4.45, SD=0.95). Additionally, these areas significantly impact perceived value (Mean=4.78, SD=0.93), prestige (Mean=4.92, SD=8.18), and attachment to the environment (Mean=4.71, SD=0.831). Residents with accessible and functional green spaces express higher satisfaction levels (Cronbach’s Alpha > 0.9). The study underscores the importance of urban greenery in improving urban living conditions and offers strategic recommendations for sustainable urban planning. Addressing a gap in literature, this research provides empirical insights into residents' perspectives within Kaduna Metropolis, contributing to academic discourse and practical urban development approaches.